International Commitments and the Rights of Women Prisoners: Challenges and Solutions (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper delves into the crucial role of global standards and commitments in upholding the rights and dignities of prisoners worldwide, with a specific focus on women prisoners. Beginning with an exploration of key international treaties such as the ICCPR and ICESR, it traces the evolution of standards through landmark documents like the Universal Declaration of Human Rights and subsequent UN directives. Focusing on specific instruments such as The Tokyo Rules, Bangkok Rules, and The Nelson Mandela Rules, the study analyzes their provisions aimed at protecting the rights of women prisoners and promoting their rehabilitation within correctional systems. Additionally, the paper highlights challenges in implementing these standards, particularly concerning women prisoners, including gender-specific vulnerabilities and discrimination. It underscores the importance of upholding human rights principles in correctional systems and calls for concerted efforts at national and international levels to ensure the effective implementation of global standards for the treatment of women prisoners, thereby promoting gender equality and justice for all.